A kind of hollow mesoporous carbon sphere self-assembled porous carbon microsphere and its preparation method

By generating carbon microspheres inside the hollow carbon spheres and performing CO2 activation, a hollow mesoporous carbon sphere self-assembled porous carbon microsphere composite material with a high specific surface area is formed, which solves the problem of low specific surface area of ​​the hollow carbon spheres and achieves a more efficient VOCs adsorption and better regeneration performance.

CN115872402BActive Publication Date: 2025-01-24WUHAN UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210824982.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-13
Publication Date
2025-01-24
Estimated Expiration
2042-07-13

AI Technical Summary

Technical Problem

The specific surface area of ​​existing hollow carbon spheres is relatively low, which limits its application in the adsorption of volatile organic compounds (VOCs).

Method used

Hollow carbon nanospheres were synthesized by sol-gel method and template method, and carbon microspheres were generated inside them by ultrasonic-hydrothermal method, and then activated in CO2 atmosphere to form self-assembled porous hollow mesoporous carbon spheres with high specific surface area. Carbon microsphere composites.

Benefits of technology

It significantly improves the surface area and adsorption capacity of the adsorption agent, enhances the adsorption and reconciliation ability of VOCs, and improves the regeneration performance of the adsorbent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003743656740000071
    Figure BDA0003743656740000071
  • Figure BDA0003743656740000081
    Figure BDA0003743656740000081
  • Figure BDA0003743656740000091
    Figure BDA0003743656740000091
Patent Text Reader

Abstract

The present invention discloses a hollow mesoporous carbon sphere self-assembled porous carbon microsphere and a preparation method thereof. The preparation method comprises the following steps: (1) preparing hollow mesoporous silicon spheres, (2) loading the hollow mesoporous silicon spheres, (3) removing SiO2 templates, (4) preparing carbon precursors, and (5) activating the carbon precursors at high temperature with CO2 to finally obtain the target product C X @HCS, where X represents the concentration of the glucose solution. The composite adsorbent material prepared by the preparation method of the present invention has a unique structure and excellent adsorption performance, especially high adsorption performance for toluene and good reproducibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a volatile organic compound adsorption purification technology, and in particular to a method for preparing a volatile organic compound adsorbent. Background Art

[0002] The emission of volatile organic compounds (VOCs) is one of the major environmental problems currently faced, which has caused serious impacts on the natural environment and human health. Adsorption technology is a promising solution for treating low-concentration VOCs pollution. Among the many VOCs treatment technologies, adsorption is currently recognized as one of the most widely used technologies. Compared with other methods, adsorption has the advantages of low cost, convenient operation, high removal efficiency and low toxicity. The principle of adsorption is to use an adsorbent with a rich pore structure to contact VOCs, and then adsorb VOCs pollutants in the atmosphere into the pores of the adsorbent under the action of the attraction and chemical bond force of the adsorbent surface. The adsorption method is divided into two forms: physical adsorption and chemical adsorption. Physical adsorption is mainly based on van der Waals force attraction, while chemical adsorption mainly relies on certain functional groups and chemical bonds on the surface of the adsorbent to make VOCs molecules bind to the adsorbent. The core of VOCs adsorption technology lies in the selection of adsorbents. Activated carbon, metal organic framework materials (MOFs), molecular sieves (zeolites), carbon nanotubes (CNTs), biochar, activated carbon fibers (ACF), etc. are all common adsorption materials. Hollow carbon sphere is a new type of porous carbon material, which has attracted wide attention due to its unique physical and chemical properties such as low specific density, large controllable internal pore volume and open framework structure. Therefore, carbon sphere has been applied to fields such as environmental governance. There have been many reports on porous carbon materials as adsorbents and catalyst carriers (such as: 2009, 21, 706-716, Chemistry of Materials), and many excellent properties have been found. It has good adsorption properties for substances such as phenol, vitamins, proteins and macromolecular dyes. As a catalyst carrier, it helps to exert the catalytic potential of the loaded catalyst. Although hollow carbon spheres have a large pore volume, their specific surface area is generally lower than the average level of current VOCs adsorbent research, which limits their application in VOCs adsorption to a certain extent.

[0003] In order to increase the specific surface area of ​​hollow carbon spheres and further improve the adsorption potential of hollow carbon spheres, it is proposed to assemble another spherical carbon material in the hollow carbon spheres. By activating the material, the specific surface area of ​​the material is further increased without affecting the pore volume, so that the material has better adsorption performance. Among the many spherical carbon materials, the hydrothermal method is a more common method to prepare carbon microspheres using biomass such as starch, glucose, sucrose, cellulose and other raw materials. This preparation method is not only simple to operate and free of pollutants, but also the prepared microspheres have good dispersibility. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a method for preparing hollow mesoporous carbon sphere self-assembled porous carbon microspheres and their application. The prepared composite adsorbent has good adsorption-desorption performance for VOCs.

[0005] In order to achieve the purpose of the above invention, the present invention synthesizes nano hollow carbon spheres by sol-gel method and template method, and the particle size is about 370-450nm and the wall thickness is about 40nm. Then, glucose is used as the carbon source, and carbon microspheres are successfully generated inside the hollow carbon spheres by ultrasound-hydrothermal method to prepare hollow mesoporous carbon sphere self-assembled porous carbon microsphere composite materials.

[0006] A method for preparing hollow mesoporous carbon sphere self-assembled porous carbon microspheres, using ordered mesoporous nano-silica spheres with through-holes as templates, adopting a hard template method to prepare hollow carbon spheres HCS with a mesoporous structure, redispersing the hollow carbon spheres HCS in a glucose or sucrose solution, performing a hydrothermal reaction in a hydrothermal reactor, and filtering, washing, and drying after natural cooling to obtain a carbon precursor;

[0007] The carbon precursor is heated at a constant speed in an inert gas atmosphere until it reacts with the continuously introduced carbon dioxide gas for activation, and then naturally cooled to room temperature in an inert gas atmosphere to obtain the final product C X @HCS, where X represents the concentration of glucose or sucrose solution.

[0008] The synthesis of ordered mesoporous nano-silica spheres with through-holes by sol-gel method has been disclosed in the prior art CN104743542B. The synthesis of nano-carbon microspheres by hydrothermal method has been disclosed in the prior art CN108975310B. The innovation of the present invention is to generate carbon microspheres with hydroxyl and carbonyl groups in hollow carbon spheres, thereby improving the adsorption capacity.

[0009] The ordered mesoporous nano-silica spheres with through-holes are prepared by the following steps: a surfactant and a co-solvent are uniformly mixed, added to ammonia water with a pH of 10, and then a silicon source precursor is added, and the mixture is fully stirred and reacted at room temperature. The obtained suspension is centrifuged, filtered, and dried to obtain the ordered mesoporous nano-silica spheres with through-holes. The surfactant is hexadecyltrimethylammonium bromide, the co-solvent is a mixed solution of deionized water and anhydrous ethanol, and the silicon source precursor is tetraethyl orthosilicate.

[0010] The preparation steps of the hollow carbon sphere HCS include: uniformly mixing ordered mesoporous nano-silica spheres with through-holes with a co-solvent, adding a phenolic resin ethanol solution, and solidifying in an oven after sufficient stirring to obtain PR@SiO2; uniformly and slowly heating up the PR@SiO2 in an inert gas atmosphere to carbonize it, and obtaining C&SiO2 after cooling to room temperature, and soaking the C&SiO2 in a hydrofluoric acid solution for etching to remove SiO2, washing it to neutrality and then drying it to obtain HCS.

[0011] The mass ratio of hexadecyltrimethylammonium bromide to tetraethyl orthosilicate is 0.32:1.868.

[0012] The mass ratio of the ordered mesoporous nano-silica spheres with through-holes to the phenolic resin ethanol solution is 1:5, and the mass fraction of the phenolic resin ethanol solution is 20wt%.

[0013] The concentration of the hydrofluoric acid solution is 5 wt %.

[0014] The concentration of the glucose solution is 0.1 mol / L to 0.5 mol / L.

[0015] The hollow carbon spheres loaded with carbon microspheres prepared by the above method have a particle size of 370-450nm, an outer wall thickness of 40nm, an outer wall composed of worm-like mesopores, and a mesopore diameter of no more than 3.34nm. The hollow carbon spheres are loaded with carbon microspheres with a particle size of 30-50nm.

[0016] The hollow carbon spheres loaded with carbon microspheres are used as raw materials for preparing Voc composite adsorption materials.

[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0018] The present invention synthesizes nano hollow carbon spheres by sol-gel method and template method, the particle size of which is about 370-450nm and the wall thickness is about 40nm. Then, glucose is used as the carbon source and carbon microspheres are successfully generated inside the hollow carbon spheres by ultrasound-hydrothermal method. After CO2 activation at 950℃, the obtained C 0.1 @HCS showed significantly better performance than HCS, with intact spherical structure, rough surface, and spherical protrusions. The carbon microspheres generated by the hydrothermal reaction of glucose adhered to the inside of HCS, increasing the microporous specific surface area of ​​HCS and providing more adsorption sites during adsorption. 0.1 @HCS retains the advantages of the hollow structure of HCS, such as large pore volume and high mass transfer efficiency, and also has abundant micropores with moderate pore size, which reduces the mass transfer resistance during the adsorption process, accelerates the adsorption of VOCs, and is more conducive to desorption, making the adsorbent have better regeneration performance. Especially in the dynamic adsorption experiment of toluene, C 0.1The toluene adsorption capacity of HCS is as high as 813 mg / g, which is 3.08 times that of HCS (264 mg / g). 0.1 @HCS has good reproducibility. Therefore, the composite adsorbent material prepared by the preparation method of the present invention has a unique structure and excellent adsorption performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a scanning electron microscope image of HCS prepared in Example 1;

[0020] Figure 2 C prepared in Example 2 0.1 @HCS scanning electron microscope image;

[0021] Figure 3 C prepared in Example 2 0.5 @HCS scanning electron microscope image;

[0022] Figure 4 is the HCS prepared in Example 1 and the C prepared in Example 2 0.1 @HCS, C 0.5 @ TEM image of HCS;

[0023] Figure 5 The nitrogen adsorption-desorption curves and pore size distribution curves of each sample prepared in Example 1 and Example 2;

[0024] Figure 6 The nitrogen adsorption-desorption curves and pore size distribution curves of CSs and CSs-950;

[0025] Figure 7 For HCS, C 0.1 @ RTIR spectra of HCS and glucose carbon microspheres CSs-950 prepared under the same activation conditions;

[0026] Figure 8 C 0.1 @HCS XPS spectra and high-resolution spectra;

[0027] Fig. 9 The HCS prepared in Example 1 and the C prepared in Example 2 0.1 @Raman spectrum of HCS;

[0028] Fig.10 are the adsorption breakthrough curves and adsorption capacities of toluene of the samples prepared in Example 1 and Example 2;

[0029] Fig.11 is the adsorption breakthrough curve and adsorption capacity of CSs-950;

[0030] Fig.12is the C prepared in Example 1 0.1 @HCS cyclic adsorption breakthrough curve of toluene;

[0031] Fig.13 is the C prepared in Example 1 0.1 @HCS adsorption amount diagram after cyclic adsorption of toluene. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.

[0033] Example 1 Preparation of hollow carbon spheres

[0034] Step 1: Dissolve 0.32 g of hexadecyltrimethylammonium bromide in a mixed solution of 56 mL of anhydrous ethanol and 106 mL of deionized water, then add 2 mL of aqueous ammonia and 2 mL of tetraethyl orthosilicate, stir at room temperature (25°C) for 8 h, centrifuge at 4000 r / min to separate the precipitate, wash with deionized water, and dry at 105°C for about 12 h to obtain hollow mesoporous silica spheres.

[0035] Step 2: Weigh 0.3 g of the hollow mesoporous silica spheres in step 1 and add them to a mixed solution of 156 mL of deionized water and 84 mL of anhydrous ethanol. Then add 1.5 g of phenolic resin ethanol solution (20 wt%). After stirring for 16 h, pour the mixture into a culture dish and cure it in an oven at 100 ° C for 24 h to obtain PR@SiO2.

[0036] Step 3: Heat the PR@SiO2 obtained in step 2 to 800°C at a heating rate of 5°C / min in a tubular furnace under a nitrogen atmosphere, calcine for 4 hours, and cool naturally to room temperature to obtain C&SiO2. Finally, etch the C&SiO2 by soaking it in 5% hydrofluoric acid solution for 24 hours to remove the SiO2 template. Recover the product by filtration, wash it with water and ethanol until it is neutral, and dry it in an oven at 105°C for 12 hours to obtain HCS.

[0037] Figure 1 The SEM image of the prepared porous hollow carbon sphere (HCS) sample is Figure 1 It can be seen from the figure that the prepared hollow carbon spheres are spherical structures with uniform particle size and smooth surface. Figure 4 As shown in a, Figure 4 a The hollow spherical structure of HCS can be clearly seen, with a particle size of approximately 370-450 nm and a wall thickness of approximately 40 nm.

[0038] Example 2 Preparation of Hollow Mesoporous Carbon Spheres Self-Assembled Porous Carbon Microspheres

[0039] Step 1: Dissolve 0.32 g of hexadecyltrimethylammonium bromide in a mixed solution of 56 mL of ethanol and 106 mL of deionized water, then add 2 mL of ammonia water and 2 mL of tetraethyl orthosilicate, stir at room temperature (25°C) for 8 h, centrifuge at 4000 r / min to separate the precipitate, wash with deionized water, and dry at 105°C for about 12 h to obtain hollow mesoporous silica spheres.

[0040] Step 2: Weigh 0.3 g of the hollow mesoporous silica spheres in step 1 and add them to a mixed solution of 156 mL of deionized water and 84 mL of anhydrous ethanol. Then add 1.5 g of phenolic resin ethanol solution (20 wt%). After stirring for 16 h, pour the mixture into a culture dish and cure it in an oven at 100 ° C for 24 h to obtain PR@SiO2.

[0041] Step 3: Heat the PR@SiO2 obtained in step 2 to 800°C at a heating rate of 5°C / min in a tubular furnace under a nitrogen atmosphere, calcine for 4 hours, and cool naturally to room temperature to obtain C&SiO2. Finally, etch the C&SiO2 by soaking it in 5% hydrofluoric acid solution for 24 hours to remove the SiO2 template. Recover the product by filtration, wash it with water and ethanol until it is neutral, and dry it in an oven at 105°C for 12 hours to obtain HCS.

[0042] Step 4: Weigh 0.1 g of HCS in step 3 and add it to 60 mL of glucose solution with concentrations of 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L and 0.5 mol / L, respectively, and mix ultrasonically for 30 min. Put it into a hydrothermal kettle with a volume of 100 mL and react it at 200 ° C for 12 h. After natural cooling, filter, wash and dry to obtain a carbon precursor.

[0043] Step 5: Place the carbon precursor in a tubular furnace and heat it to 950°C at a heating rate of 10°C / min in a nitrogen atmosphere, introduce 60mL / min of CO2 gas for 2 hours, and then replace nitrogen to cool to room temperature to obtain the final product C. X @HCS, where X represents the concentration of glucose solution.

[0044] Figure 2 and Figure 3 For the preparation of C 0.1 @HCS and C 0.5 @ SEM image of HCS sample, after CO2 activation, C 0.1The spherical structure of HCS remains intact, but the surface becomes rough and has some spherical protrusions. This is because some carbon microspheres generated by the hydrothermal reaction of glucose adhere to the surface of HCS. The growth of carbon microspheres conforms to the LaMer model. As the concentration of glucose solution increases, the particle size of carbon microspheres also increases. When the concentration of glucose solution is 0.5 mol / L, the particle size distribution of the generated carbon microspheres is uneven, ranging from about 500 nm to 1 μm, which is much larger than the particle size of HCS and cannot be loaded on the surface or inside of HCS. 0.1 @HCS and C 0.5 TEM photos of HCS Figure 4 b and Figure 4 As shown in c, Figure 4 b It can be clearly seen that the particle size of the carbon microspheres hydrothermally generated by 0.1 mol / L glucose solution is about 30-40 nm, and they are successfully generated inside HCS. Therefore, after activation, the micropore specific surface area of ​​HCS can be greatly increased, providing more adsorption sites during adsorption. Figure 4 c is the carbon microspheres hydrothermally generated from 0.5 mol / L glucose solution, which are solid spheres with a particle size of about 1 μm, consistent with the SEM results. Figure 4 d is C 0.1 High-resolution image of HCS, showing that the outer wall of HCS is composed of worm-like mesopores with graphite structures appearing at the edges.

[0045] Comparative Example 1 Preparation of activated carbon microspheres

[0046] Step 1: Measure 60 mL of a glucose solution with a concentration of 0.1 mol / L, ultrasonicate it for 30 min, put it into a hydrothermal kettle with a volume of 100 mL, and hydrothermally react it at 200° C. for 12 h; after natural cooling, filter, wash, and dry to obtain a carbon precursor.

[0047] Step 2: Place the carbon precursor in a tubular furnace and heat it to 950°C at a heating rate of 10°C / min in a nitrogen atmosphere. Pass 60mL / min of CO2 gas for 2 hours. After the end, replace the nitrogen and naturally cool to room temperature to obtain the final product CSs-950.

[0048] Comparative Example 2 Preparation of Carbon Microspheres

[0049] Step 1: Measure 60 mL of a glucose solution with a concentration of 0.1 mol / L, ultrasonicate it for 30 min, put it into a hydrothermal kettle with a volume of 100 mL, and hydrothermally react it at 200° C. for 12 h; after natural cooling, filter, wash, and dry to obtain a carbon precursor CSs.

[0050] The nitrogen adsorption-desorption isotherms of the samples prepared in Example 1 and Example 2 were measured at 77 K using an ASAP2020 analyzer (Micromeritics), and the specific surface area (S BET ). The pore size distribution and average pore size of the sample were obtained by the BJH model through the adsorption branch of the isotherm. The total pore volume (V0) was calculated based on the amount of nitrogen adsorbed at a relative pressure of 0.99.

[0051] Figure 5 a and Figure 5 b is HCS and C X @Nitrogen adsorption-desorption curves and pore size distribution curves of HCS after CO2 gas activation at 950℃. According to the classification of the International Union of Pure and Applied Chemistry (IUPAC), HCS, C 0.1 @HCS, C 0.2 @HCS and C 0.3 @HCS both show typical type IV isotherms, which correspond to the characteristics of mesoporous materials. The difference is that HCS and C X The hysteresis loop type of @HCS changes from H2 to H4, indicating that C X @HCS has become a micro-mesoporous material. 0.4 @HCS and C 0.5 @HCS shows a type I isotherm, indicating that C 0.4 @HCS and C 0.5 @HCS has a large proportion of micropores. Compared with HCS, C X The nitrogen adsorption capacity of HCS in the low pressure region (P / P0<0.1) increased significantly, and with the increase of the particle size of glucose carbon microspheres, C X The hysteresis loop of @HCS gradually decreases from Figure 5 It can also be seen in b that HCS and C X @HCS peaks at 3.6nm, but the proportion gradually decreases. X @HCS also shows an obvious peak at less than 2nm, indicating that when CO2 is used for activation, a large number of micropores are formed in the sample, which is more conducive to the adsorption of VOCs.

[0052] As shown in Table 1, the micropore volume (V mic ) and micropore specific surface area (S mic), the pore size distribution and average pore size of each sample were obtained by using the BJH model through the adsorption branch of the isotherm. The total pore volume (V0) was calculated based on the amount of nitrogen adsorbed at a relative pressure of 0.99. The specific surface area, pore volume and average pore size of each sample prepared in Example 1 and Example 2 are shown in the following table. The specific surface area and micropore specific surface area of ​​HCS are 1268m 2 / g, 243m 2 / g increased to 1945m 2 / g and 1134m 2 / g(C 0.1 @HCS), the pore volume is 1.319cm 3 / g increases to 1.627cm 3 / g, the larger specific surface area and pore volume can provide a large number of adsorption sites for the adsorbate molecules, thereby increasing the adsorption amount. 0.1 The average pore size of @HCS decreased from 5.16nm to 3.34nm, but it is larger than that of C 0.2 @HCS and other samples have an average pore size. Its larger pore size can reduce the mass transfer resistance during the adsorption process, accelerate the adsorption of VOCs, and is more conducive to desorption, so that the adsorbent has better regeneration performance.

[0053] Table 1

[0054]

[0055] The nitrogen adsorption-desorption curves and pore size distribution curves of CSs and CSs-950 were measured ( Figure 6 a~ Figure 6 d), and the specific surface area, pore volume and average pore size of CSs and CSs-950 in Table 2. The specific surface area and pore volume of the carbon microspheres generated by glucose hydrothermal reaction are very small, and can be approximately regarded as solid spheres. After the carbon microspheres are activated, the specific surface area and pore volume increase to 2352 m 2 / g and 1.321cm 3 / g, of which the micropore specific surface area exceeds 70%, indicating that carbon microspheres have good pore-forming potential and can make up for the shortcoming of small number of micropores in HCS after combining with HCS.

[0056] Table 2 Structural parameters of CSs-950 and CSs

[0057]

[0058] According to HCS, C 0.1 RTIR spectra of HCS and glucose carbon microspheres CSs-950 prepared under the same activation conditions ( Figure 7 ). Wave number at 3440cm -1The broad peak corresponds to the stretching vibration peak of OH, 2930 cm -1 and 2855cm -1 The antisymmetric and symmetric stretching vibration peaks of CH corresponding to the methyl group, 1628 cm -1 Corresponding to the stretching vibration peak of C=O, 1210cm -1 The stretching vibration peak of COC is at 650cm -1 The out-of-plane bending vibration of the aromatic ring CH indicates that dehydration condensation and aromatic ring formation occurred during the hydrothermal reaction of glucose, and the functional groups of the carbon microspheres are mainly -OH and C=O. 0.1 The surface OH and C=O absorption peaks of HCS were significantly weakened, the CH absorption peak disappeared, and the functional groups on the surface of carbon microspheres were significantly reduced, which was similar to the surface of HCS. Combined with the TEM results, it can be inferred that glucose carbon microspheres were generated inside HCS after ultrasonic hydrothermal treatment and the envisioned structure was obtained.

[0059] C 0.1 The XPS spectrum and high-resolution spectrum of @HCS are as follows Figure 8 As shown, from Figure 8 As can be seen in a, the typical peaks of the sample are C1s and O1s, indicating that the sample is mainly composed of C and O elements. The high-resolution spectrum of C1s can be divided into three peaks after deconvolution and correction, namely CC / C=C bond (284.8eV), CO bond (286.2eV) and C=O bond (289.10eV) ( Figure 8 b), O1s can be divided into C=O bond (532.0 eV), C-OH / COC (533.2 eV) and HOH bond (536.1 eV) after fitting ( Figure 8 c), where HOH may be due to oxygen or water adsorbed on the sample surface, and the peak fitting results are consistent with the FTIR results.

[0060] The structure of carbon spheres was further studied using Raman spectroscopy, such as Fig. 9 HCS and C 0.1 @HCS is 1360cm -1 (D peak) and 1580cm -1 (G peak) There are two significant peaks, the D peak corresponds to the defect / disordered structure of the material, and the G peak corresponds to the conjugated structure of the material. It is the in-plane vibration peak of carbon atoms in graphite microcrystals. It is usually expressed as the intensity ratio of the two peaks (I D / I G ) measures the degree of graphitization of the sample. The larger the ratio, the greater the irregularity of the carbon material. 0.1 @HCS D / I G 0.89 and 1.09 respectively. Compared with HCS, C 0.1@HCS D / I G Increase, indicating C 0.1 @HCS has a higher degree of irregularity. This is related to the activation of CO2 gas. At a high temperature of 950°C, CO2 reacts with the carbon precursor, consuming tar and uncarbonized substances, thereby increasing the degree of defects in the material, and thus having a stronger adsorption capacity, which is consistent with the nitrogen adsorption-desorption curve of the sample and the adsorption experimental results.

[0061] Test 1: The products of the above embodiments and comparative examples were subjected to a toluene adsorption test.

[0062] In order to test the adsorption performance of the sample, a dynamic adsorption experiment of toluene was carried out on a fixed bed adsorption device with toluene as the target. The dynamic adsorption experimental device consists of a gas distribution system, an adsorption system and a concentration detection system. A certain flow rate of N2 and O2 (N2 / O2=4:1) simulated air as a carrier gas, and the toluene injected by a micro-injection pump (KD Scientific, USA) was mixed evenly and entered the fixed bed adsorption column (inner diameter of 4mm) for adsorption reaction. The gas after the reaction entered the gas chromatograph (GC9790Ⅱ) with a flame ionization detector (FID) for detection. The toluene concentration was injected into liquid toluene by a syringe pump, evaporated in a heating tube, and then diluted and calibrated with carrier gas. In the experiment, the adsorbent weight was 50mg, the adsorption temperature was 25℃, the flow rate was set to 100mL / min, and the toluene concentration was 1000ppm. Before adsorption, the sample was treated in a nitrogen gas flow at 110℃ for 1h to remove impurities and moisture adsorbed in the adsorbent.

[0063] The adsorption amount of toluene Q (mg / g) is calculated by formula (1):

[0064]

[0065] Where F is the carrier gas flow rate, M is the molar mass of toluene, C0 and C t are the initial concentration of toluene and the concentration of toluene at time t, t s is the time of adsorption saturation, and m is the mass of the adsorbent.

[0066] from Fig.10 It can be seen that each sample C in Example 2 X The change of adsorption capacity of @HCS for toluene shows a similar trend to the change of specific surface area of ​​the material, where C 0.1@HCS has the largest toluene adsorption capacity, up to 813 mg / g, which is 3.08 times the adsorption capacity of HCS in Example 1 (264 mg / g), indicating that loading carbon microspheres on HCS can greatly improve the adsorption performance of the material, making the material have excellent adsorption capacity compared with other materials, as shown in Table 3 below. Combined with Table 1, it can be seen that the total specific surface area of ​​HCS is 0.4 @HCS is similar, the micropore specific surface area is only C 0.4 @22% of HCS, but its adsorption capacity can be increased to C 0.4 @68% of HCS, this is because HCS has a larger pore volume (1.319 cm 3 / g), providing certain adsorption sites. As shown in Table 1, C 0.1 @HCS and C 0.3 @HCS, C 0.4 @HCS micropore specific surface area is not much different, but the adsorption capacity is increased by 330mg / g and 424mg / g respectively, mainly due to C 0.1 After activation, the pore volume of HCS increases and it has more mesoporous structures, which greatly improves the adsorption capacity of toluene. Fig.11 The adsorption breakthrough curve and adsorption capacity of CSs-950. CSs-950 has the largest specific surface area and micropore specific surface area among all samples, but its toluene adsorption capacity is only 0.1 @HCS showed no maximum adsorption capacity. In summary, the hierarchical pore structure of micropores and mesopores and the large pore volume are the main reasons for the adsorption of C 0.1 This is the main reason why HCS exhibits the best performance in the toluene dynamic adsorption experiment.

[0067] Table 3

[0068]

[0069] Test 2: Test a C with the best adsorption capacity 0.1 @HCS conducts cyclic adsorption-desorption experimental tests.

[0070] Another important indicator for evaluating the performance of the adsorbent is the reusability of the adsorbent. In order to test the regeneration performance of the sample, a cyclic adsorption-desorption experiment was performed on the sample. After the adsorption reached equilibrium, the toluene was turned off, and the fixed bed adsorption device was heated to 200°C and maintained for 2 hours for thermal desorption. After the desorption was completed, the device was cooled to 25°C for the next adsorption experiment.

[0071] like Fig.12 , Fig.13 As shown, 20 mg of C 0.1@HCS conducted a cyclic adsorption-desorption experiment. After the adsorption reached saturation and stabilized for 15 minutes, the toluene was turned off and only nitrogen was introduced and the temperature was increased for desorption. After 2 hours of treatment, the temperature was lowered to 25°C for the next round of adsorption experiment. 0.1 @HCS 8-cycle adsorption breakthrough curve Fig.12 As shown, in the 8 cycle experiments, the adsorbent can basically maintain close to 100% adsorption efficiency in the first 25 minutes. The breakthrough time of the first adsorption is 35 minutes. After one cycle, the breakthrough time is shortened to 30 minutes. In the subsequent cycle experiments, the breakthrough time is also maintained at 30 minutes, and saturation is reached in 45 minutes. This shows that the adsorption performance of the adsorbent has declined after the regeneration experiment, but the degree of decline is not large. Fig.13 C 0.1 @HCS showed that the adsorption capacity of the adsorbent in the 8-cycle experiment decreased from 827 mg / g to 799 mg / g after one cycle, a decrease of 3.4%, and then tended to be stable. After 7 adsorption-desorption experiments, the adsorption capacity could be maintained at more than 90%, indicating that the adsorbent has good regeneration performance.

Claims

1. A method for preparing hollow mesoporous carbon sphere self-assembled porous carbon microspheres, characterized in that: Using ordered mesoporous nano-silica spheres with through-holes as templates, a hard template method was used to prepare hollow carbon spheres HCS with a mesoporous structure. The hollow carbon spheres HCS were redispersed in a glucose or sucrose solution, and a hydrothermal reaction was carried out in a hydrothermal reactor. After natural cooling, the carbon precursor was obtained by filtration, washing, and drying. The carbon precursor was uniformly heated to 950°C in an inert gas atmosphere and activated by continuous introduction of carbon dioxide gas, and then naturally cooled to room temperature in an inert gas atmosphere to obtain the final product C. X @HCS, where X represents the concentration of glucose or sucrose solution; The concentration of the glucose solution is 0.1 mol / L; The hollow carbon sphere has a particle size of 370-450nm, an outer wall thickness of 40nm, an outer wall composed of worm-like mesopores, and a mesopore diameter of no more than 3.34nm. The hollow carbon sphere is loaded with carbon microspheres with a particle size of 30-50nm. The hollow mesoporous carbon sphere self-assembles porous carbon microspheres with a micropore-mesopore hierarchical pore structure. The ordered mesoporous nano-silica spheres with through-hole channels are prepared by the following steps: uniformly mixing a surfactant and a co-solvent, adding them to ammonia water with a pH of 10, and then adding a silicon source precursor, fully stirring and reacting at room temperature, and the obtained suspension is centrifuged, filtered, and dried to obtain ordered mesoporous nano-silica spheres with through-hole channels, wherein the surfactant is hexadecyltrimethylammonium bromide, the co-solvent is a mixed solution of deionized water and anhydrous ethanol, and the silicon source precursor is tetraethyl orthosilicate; The preparation steps of the hollow carbon sphere HCS include: uniformly mixing ordered mesoporous nano-silica spheres with through-holes with a co-solvent, adding a phenolic resin ethanol solution, and solidifying in an oven after sufficient stirring to obtain PR@SiO2; uniformly and slowly heating up the PR@SiO2 in an inert gas atmosphere to carbonize it, and obtaining C&SiO2 after cooling to room temperature, and soaking the C&SiO2 in a hydrofluoric acid solution for etching to remove SiO2, washing it to neutrality and then drying it to obtain HCS.

2. The method for preparing hollow mesoporous carbon sphere self-assembled porous carbon microspheres according to claim 1, characterized in that: The mass ratio of hexadecyltrimethylammonium bromide to tetraethyl orthosilicate is 0.32:1.

868.

3. The method for preparing hollow mesoporous carbon sphere self-assembled porous carbon microspheres according to claim 2, characterized in that: The mass ratio of the ordered mesoporous nano-silica spheres with through-holes to the phenolic resin ethanol solution is 1:5, and the mass fraction of the phenolic resin ethanol solution is 20wt%.

4. The method for preparing hollow mesoporous carbon sphere self-assembled porous carbon microspheres according to claim 3, characterized in that: The concentration of the hydrofluoric acid solution is 5 wt %.

5. Hollow mesoporous carbon sphere self-assembled porous carbon microspheres prepared according to the method according to any one of claims 1 to 4.

6. Use of the hollow mesoporous carbon sphere self-assembled porous carbon microspheres as claimed in claim 5 in the preparation of Voc composite adsorption materials.

Citation Information

Patent Citations

  • A hollow mesoporous carbon sphere and its preparation method

    CN104743542B

  • A method for preparing pressure-assisted size-controllable hydrothermal carbon spheres and the prepared hydrothermal carbon spheres

    CN108975310B

  • Hollow mesoporous carbon ball and preparation method thereof

    CN104743542A

  • Preparation method for pressure-assisted size-controllable hydrothermal carbon spheres and prepared hydrothermal carbon spheres

    CN108975310A